Canadian retirement savings programs and Russian pension reform - Joel Fried (The University of Western Ontario, Department of Economics, 2001)
This paper surveys the evolution of the Canadian pension system to provide possible ideas for pension reform in Russia. Particular emphasis is placed on the Canadian voluntary, tax assisted retirement savings plans. Such plans can be used as an incentive mechanism to draw savings into the financial system and, properly structured, provide a source of capital to small business. It is argued that instituting a 'foreign property rule' limiting foreign assets in such plans is especially unhelpful in supporting the exchange rate, domestic investment, or financial market development. What matters for the exchange rate is whether the assets held are or are not hedged into domestic currency, a decision based on attitudes toward the central bank and not on the possible origin of the assets. With the ability to invest in foreign assets, and a tax deferral system similar to Canada, a likely source of funds to be deposited in such Russian plans could be from the barren foreign currency held by Russians outside of the financial system.
Keywords: 330; Alterssicherung; Gesetzliche Rentenversicherung; Rentenreform; Kanada; Russland